Differences between fast and slow muscles in scallops revealed through proteomics and transcriptomics - Xiujun Sun; Zhihong Liu; Biao Wu; Liqing Zhou; Qi Wang; Wei Wu; Aiguo Yang (BMC Genomics, 2018)
Abstract Background Scallops possess striated and catch adductor muscles, which have different structure and contractile properties. The striated muscle contracts very quickly for swimming, whereas the smooth catch muscle can keep the shells closed for long periods with little expenditure of energy. In this study, we performed proteomic and transcriptomic analyses of differences between the striated (fast) and catch (slow) adductor muscles in Yesso scallop Patinopecten yessoensis. Results Transcriptomic analysis reveals 1316 upregulated and 8239 downregulated genes in slow compared to fast adductor muscle. For the same comparison, iTRAQ-based proteomics reveals 474 differentially expressed proteins (DEPs), 198 up- and 276 downregulated. These DEPs mainly comprise muscle-specific proteins of the sarcoplasmic reticulum, extracellular matrix, and metabolic pathways. A group of conventional muscle proteins—myosin heavy chain, myosin regulatory light chain, myosin essential light chain, and troponin—are enriched in fast muscle. In contrast, paramyosin, twitchin, and catchin are preferentially expressed in slow muscle. The association analysis of proteomic and transcriptomic data provides the evidences of regulatory events at the transcriptional and posttranscriptional levels in fast and slow muscles. Among 1236 differentially expressed unigenes, 22.7% show a similar regulation of mRNA levels and protein abundances. In contrast, more unigenes (53.2%) exhibit striking differences between gene expression and protein abundances in the two muscles, which indicates the existence of fiber-type specific, posttranscriptional regulatory events in most of myofibrillar proteins, such as myosin heavy chain, titin, troponin, and twitchin. Conclusions This first, global view of protein and mRNA expression levels in scallop fast and slow muscles reveal that regulatory mechanisms at the transcriptional and posttranscriptional levels are essential in the maintenance of muscle structure and function. The existence of fiber-type specific, posttranscriptional regulatory mechanisms in myofibrillar proteins will greatly improve our understanding of the molecular basis of muscle contraction and its regulation in non-model invertebrates.